Model development for microbial spoilage of packaged fresh‒cut salad products using temperature and in-package CO2 levels as predictor variables. (October 2019) - Kapetanakou, Anastasia E.; Taoukis, Petros; Skandamis, Panagiotis N.
Abstract: The objective of this study was to develop a model system for the prediction of the impact of temperature and in-package % CO2 on the microbial spoilage of fresh‒cut vegetables with high respiration rate independent of packaging characteristics and post-harvest physiology. Model development was based on study of rocket pulp stored under 0–20% O2 : 20-0% CO2 : 80% N2 at 0–15 °C. Growth of pseudomonads and lactic acid bacteria (LAB) was primary modelled by Baranyi model, while growth rate was further modeled as a function of storage temperature and % CO2 by a polynomial model. Both growth models were validated against various fresh‒cut vegetables of high respiration rate, modified atmosphere packaging, and packaging films, under isothermal and dynamic temperature conditions. Variations of gas concentration of rocket pulp was eliminated or significantly decreased (p < 0.05), verifying our initial hypothesis. Pseudomonads were the dominant spoilage microorganisms in rocket pulp, while LAB were significantly favored (p < 0.05), as temperature and % CO2 increased. Both models had acceptable performance, presenting pRE (proportion of relative error) ≥ 0.70, bias factor of 0.99–1.00 and accuracy factor of 1.04–1.07. The developed empirical models in rocket pulp may be a useful tool to predict pseudomonads and LAB behavior in commercial packages of different fresh‒cut salads such as rocket, romaine, and iceberg lettuce. Highlights: Pseudomonads were the dominant spoilage microorganism in rocket pulp. LAB were significantly favored, as the storage temperature and % CO2 increased. Variations of gas concentrations of rocket pulp was eliminated or significantly decreased. Both polynomial models (pseudomonads and LAB) may be applicable in a variety of fresh‒cut salads.